2019
DOI: 10.1038/s41598-019-46242-4
|View full text |Cite
|
Sign up to set email alerts
|

Light triggered encapsulation and release of C60 with a photoswitchable TPE-based supramolecular tweezers

Abstract: Stimuli responsive hosts for C 60 can control its binding and release on demand. A photoswitchable TPE based supramolecular host can encapsulate C 60 in the Z -form with a markedly different visual change in the colour. In addition, the Z -1 bound C 60 has been characterized by various spectroscopic methods and mass spectrometry. Upon exposure to visible light (>490 nm), the host switches to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Recently, we have studied the selective capture of C 60 using smaller TPE derivatives. 50 Thus, we studied the interaction of both trans-and cis-isomers of TPE-1 with carboxylic acid functionalized MWCNTs. For trans-TPE-1 in THF, increasing the amount of MWCNT in the solution (MWCNT was dispersed in the THF solution) led to a decrease in peak intensity at 405 nm in the UV−vis spectrum, along with an 8 nm red-shift and the formation of a new band at 580 nm (Figures 3A and S12A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have studied the selective capture of C 60 using smaller TPE derivatives. 50 Thus, we studied the interaction of both trans-and cis-isomers of TPE-1 with carboxylic acid functionalized MWCNTs. For trans-TPE-1 in THF, increasing the amount of MWCNT in the solution (MWCNT was dispersed in the THF solution) led to a decrease in peak intensity at 405 nm in the UV−vis spectrum, along with an 8 nm red-shift and the formation of a new band at 580 nm (Figures 3A and S12A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The tetraphenylethylene (TPE) unit with four phenyl groups, a well-studied system for its aggregation-induced emission (AIE) properties, serves as an excellent candidate as a building block for the receptors of carbon-based frameworks. 49,50 Among common photochromic molecules (diarylethenes, 51 spiropyrans, 52 oxazines, 53 stilbenes, 54 and azobenzenes), azobenzenes respond to two main external stimuli, light and heat, to reversibly switch between the isomers with different properties. Azobenzene switches from the thermodynamically favored trans-isomer to the cis-isomer upon exposure to ultraviolet (UV) light.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular switches such as diarylethene, spyropyran, , and azobenzene have gained considerable attention owing to their potential use in molecular devices to switch the mechanical and optical properties of a wide range of materials as well as provide a means for controlling the catalytic activity by light. Azobenzenes are extensively used due to their robustness, easy functionalization, and large changes in the geometry and the associated molecular properties upon exposure to light . Cyclic azobenzenes often display enhanced switching compared to their acyclic analogs. , They are thermally stable in the E -form and convert into the Z -form upon exposure to UV light.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tetraphenylethene (TPE) and its derivatives are weakly emissive or nonemissive in dilute solutions, but they emit efficiently in the aggregated or solid states, which may arise due to restricted intramolecular rotation (RIR). Fascinated by this intriguing phenomenon, a large number of AIEgens, with diversified architectures and versatile properties, have been generated and applied in organic light-emitting devices, biological imaging, organelles imaging, and drug delivery monitoring. In 2019, Yang and co-workers reported that in the presence of Hg 2+ , the RIR will be effected by host–guest interaction between the TPE bridge and the pillar[6]­arene functionalized arms . However, to the best of our knowledge, to date, only few examples of MIM-based AIE active reversible molecular switching have been reported to be operational in aqueous media. In our previous work, we described that TPE–calix[4]­arene-functionalized MIM-based reversible molecular switching supramolecular amphiphiles manifested their fluorescence emission, distinct nanostructures, and gelation properties could be induced by the multinoncovalent interactions during the self-assembly processes .…”
Section: Introductionmentioning
confidence: 99%